Craft, money and mercy: an apothecary's self-portrait in sixteenth-century Bologna1. Issue 2 (3rd April 2017) - Di Gennaro Splendore, Barbara
SUMMARY: The apothecary occupied a liminal position in early modern society between profit and healing. Finding ways to distance their public image from trade was a common problem for apothecaries across Europe. This article uses the case of a Bolognese apothecary, Filippo Pastarino, to address the question of how early modern apothecaries chose to represent themselves to political authorities and to the wider public. 'Mercy', alongside 'craft', was a pillar of apothecaries' social identity. By contrast, no matter how central financial transactions ('money') were to their activity, apothecaries did not want to be perceived as merchants. Thus, the assistance and advice apothecaries provided to patients and customers resulted as central aspects of their social role. In this context, Bolognese apothecaries aimed to defend their current status, which had been challenged by naturalist Ulysses Aldrovandi, city authorities and local monasteries. However, Pastarino's claims can also be seen as antecedents to the self-legitimizing strategy that seventeenth-century artisans deployed when faced with the need to enhance their new status as natural philosophers. The present study attributes a name, a date of birth and a shop to Filippo Pastarino, revising previous interpretations. More broadly, by focusing on how these artisans defended their position in the city it enriches our understanding of the self-representation of apothecaries.